AN RESEARCH IN ELAZIG RELATED TO OPINIONS ABOUT PROFESSIONAL ETHICS OF MEMBERS OF ACCOUNTING PROFESSION - Gamze Ayça KAYA (Fırat University, 2019)
Like in any occupation, ethics is also important in accounting. Thus, ethical principles are regulated both in national and international mediums. The members of accounting occupation should act in accordance with the professional ethics. Union of Chambers of Certified Public Accountants and Sworn-In Certified Public Accountants of Turkey (TURMOB) has determined the ethical principles that the members of accounting profession shall practice. These ethical principles are integrity, objectivity, professional competence and diligence, confidentiality and professional behavior. The aim of this study is to determine the level of knowledge of the members of the accounting profession in Elazığ, regarding professional ethics, and their thoughts and perception of the professional ethics, the reasons why they either do practice or do not practice professional ethics on whatever occasions, their compliance level with the professional ethics and the advantages and disadvantages of practicing professional ethics. Survey method has been used to collect the data for the study. According to the data of The Elazığ-Bingöl Chamber of Independent Accountants and Financial Advisors, there are a total of 82 accounting professionals in these cities. 5 of these are in Bingöl, and 77 of them are working in Elazığ. The data for the study was collected from 74 professionals who are registered to Elazığ-Bingöl Chamber of independent accountants and financial advisors. The survey consists of 22 questions and 24 statements. The survey was conducted face to face with the prepared survey form and the results were evaluated using IBM SPSS Statistics 20 Software. According to the results of this study, it's been determined that the professionals always comply with the professional ethics and the supervisions regarding the professional ethical principles are not adequate.